2019
DOI: 10.35188/unu-wider/2019/727-9
|View full text |Cite
|
Sign up to set email alerts
|

Winning or buying hearts and minds?: Cash transfers and political attitudes in Pakistan

Abstract: provides economic analysis and policy advice with the aim of promoting sustainable and equitable development. The Institute began operations in 1985 in Helsinki, Finland, as the first research and training centre of the United Nations University. Today it is a unique blend of think tank, research institute, and UN agency-providing a range of services from policy advice to governments as well as freely available original research. The Institute is funded through income from an endowment fund with additional con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The study shows that poverty has remained particularly high in areas not affected by the conflict due to the deployment of troops and larger aid flows to conflict areas (see also Bove and Gavrilova 2014). Ghorpade et al (2016) show, however, that conflict events across districts in Afghanistan have been associated with the probability of household using harmful coping strategies to deal with poverty shocks. Among these few studies, none have focussed on the development and welfare impact of the conflict on young adults.…”
Section: Afghanistanmentioning
confidence: 91%
“…The study shows that poverty has remained particularly high in areas not affected by the conflict due to the deployment of troops and larger aid flows to conflict areas (see also Bove and Gavrilova 2014). Ghorpade et al (2016) show, however, that conflict events across districts in Afghanistan have been associated with the probability of household using harmful coping strategies to deal with poverty shocks. Among these few studies, none have focussed on the development and welfare impact of the conflict on young adults.…”
Section: Afghanistanmentioning
confidence: 91%
“…Repression comes at a cost because policing and targeting civilians requires manpower and intelligence, and may trigger organized rebellion against the group, forcing it to fight on several fronts (Arjona 2016;Kaplan 2017;Kasfir 2015). Insurgent groups may nonetheless engage in predatory behaviour and exercise violence and repression against civilians when they are defeated in combat and lose territory (Wood 2014), or when they have access to external 18 A parallel literature has analysed the effect of government social spending, aid, and economic policy on the incidence and outbreak of violent conflicts (Crost et al 2014;Fearon et al 2009;Justino 2015;Justino and Martonaro 2018), civic unrest (Gupte et al 2014;Iacoella et al 2021;Justino and Martorano 2019;McCulloch et al 2022), and attitudes towards the state in post-conflict settings (Ghorpade and Justino 2019). 19 To note that the provision of public goods and services is useful to improve institutional capacity and social contracts in both democracies and autocracies.…”
Section: Violence Against Civiliansmentioning
confidence: 99%
“…Evans et al (2019) found that cash transfers in Tanzania increased trust in elected leaders. A study conducted by Ghorpade and Justino (2019) observed that the benefits of the Benazir Income Support Programme in Pakistan increased satisfaction of the citizens with the government. Similarly, Kumar et al (2021) and Mishra and Attri (2020) confirmed that households who benefitted from various government welfare schemes showed greater trust in the state government.…”
Section: Review Of Literaturementioning
confidence: 99%